Conservation Strategy and Innovation of Indigenous Indonesian Orchids for Sustainable Practice - Khoirul Arifin, Fathur; Nuraini, Latifa; Purba, Endang Rinawati (Universitas Brawijaya, 2025)
Indigenous Indonesian orchids are one of the biodiversity assets that are threatened with extinction due to habitat destruction, over-exploitation, and climate change factors. Conservation efforts have been developed to protect indigenous orchids in their natural habitat and outside their habitat. Bibliometric analysis is one of the popular tools used to analyse a number of scientific articles. VOSviewer is a method that shows that this study focuses on themes such as biodiversity, propagation technology, and ecotourism utilisation. The purpose of this study is to determine the research trend on the topic of strategy and innovation for the conservation of indigenous Indonesian orchids from year to year and to visualise research related to this topic for sustainable use. Data were collected from the SCOPUS database from 2018 to 2024 using the keywords